An Analysis of Studies on Teaching and Learning Reading in Indonesia - delfi, sofia; Yamat, Hamidah (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2017)
Various studies on teaching and learning reading in Indonesia have been conducted. In order to know the strengths and the weaknesses of the studies, a thorough study is needed to be conducted. This article is based on a critical analysis on teaching and learning reading in Indonesia for a study “a Case Study on Two Indonesian Learners’ Extensive Reading in English Experiences towards Developing Reading Competency”.  It aimed to answer: (1) What were the strengths and the weaknesses of the studies on teaching and learning reading in 2003 to 2013? (2) How were the studies similar and/ or different from the current study”? The critical analysis was conducted by studying twenty articles from 2003 until 2013. The studies were analyzed critically in terms of the strengths and the weaknesses. The findings of the analysis are;  (1) The strengths of the studies on teaching and learning reading in 2003 to 2013 were in terms of the topic of the studies indicating that learning English in Indonesian context and the studies on extensive reading were developed gradually. The weaknesses were in terms of the focus of   extensive reading and the variation of the research design. (2) The studies were similar with the current study in terms of the concept of extensive reading and the research design. This condition might be considered as an opportunity for the following researchers to conduct a research about learners’ experiences on extensive reading. It is suggested that that teachers, lecturers and the policy makers on language learning concern about how extensive reading is implemented.